A comparison of gluteus medius, gluteus minimus and tensor facia latae muscle activation during gait in post-menopausal women with and without greater trochanteric pain syndrome. (April 2017) - Ganderton, Charlotte; Pizzari, Tania; Harle, Tanya; Cook, Jill; Semciw, Adam
Abstract: The effect of greater trochanteric pain syndrome (GTPS) on gluteus medius (GMed) and minimus (GMin) activation in post-menopausal women is unknown. The aim of this study was to compare segmental muscle activation and variability of the GMed, GMin and tensor fascia latae (TFL) during gait in post-menopausal women with and without GTPS. Intramuscular electrodes were inserted into segments of GMin (x2) and GMed (x3) and a surface electrode placed on TFL. Ten control participants and 8 with GTPS completed six walking trials. Peak amplitude, average amplitude and time to peak from each phase of the gait cycle (0–30%, 30%- toe off (TO), total stance and swing) were compared between groups using independent t -tests and effect-size (ES) calculations. Variability of muscle activation was calculated using the mean coefficient of variation (CV). Reversal of anterior GMin electromyographic burst pattern and greater average muscle activity was found in the GTPS group compared to controls: 0-TO for anterior GMin (p < 0.05), anterior and middle GMed (p < 0.01); 0–30% for posterior GMin (p < 0.01) and GMed (p < 0.05). No significant differences were identified in TFL. Overall, this study found increased segmental gluteal muscle activation, decreased hip abduction strength, and reduced variability in muscle activation in post-menopausal women with GTPS, compared with controls.